Book review: Gieseking, J.J., Mangold, W., Kats, C., Low, S. and Saegert, S., editors, 2014: The People, Place and Space Reader. (July 2018) - Fontefrancesco, Michele F.
Gieseking, J.J., Mangold, W., Kats, C., Low, S. and Saegert, S., editors, 2014: The People, Place and Space Reader . New York, NY and Oxon: Routledge. xxxiv + 446 pp. £46.99 (Paperback). ISBN: 9780415664974.